Developing New Market Strategy from Supply Chain Management Perspective: A Case of Jotun in Brazil - Mawari, Emmanuel K.; Yebabe, Yohannes; Mosess, Benjamin (International Journal of Supply Chain Management, 2014)
This paper proposes to develop a supply chain managemnt strategy framework that will be unable Jotun to better configure its operations in Brazil.